2011
DOI: 10.1128/jvi.05149-11
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Baculovirus Sulfhydryl Oxidase, a Highly Divergent Member of the Erv Flavoenzyme Family

Abstract: Genomes of nucleocytoplasmic large DNA viruses (NCLDVs) encode enzymes that catalyze the formation of disulfide bonds between cysteine amino acid residues in proteins, a function essential for the proper assembly and propagation of NCLDV virions. Recently, a catalyst of disulfide formation was identified in baculoviruses, a group of large double-stranded DNA viruses considered phylogenetically distinct from NCLDVs. The NCLDV and baculovirus disulfide catalysts are flavin adenine dinucleotide (FAD)-binding sulf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 49 publications
5
15
0
Order By: Relevance
“…We previously observed that the manner in which the FAD-binding fold of the viral sulfhydryl oxidases assembles into quaternary structures varies widely among NCLDVs and other large viruses [7], [10]. In the current study, we show that viral sulfhydryl oxidases exhibit tertiary as well as quaternary structural innovation.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…We previously observed that the manner in which the FAD-binding fold of the viral sulfhydryl oxidases assembles into quaternary structures varies widely among NCLDVs and other large viruses [7], [10]. In the current study, we show that viral sulfhydryl oxidases exhibit tertiary as well as quaternary structural innovation.…”
Section: Discussionsupporting
confidence: 62%
“…Specifically, the African swine fever virus sulfhydryl oxidase, pB119L, and baculovirus Ac92 both use orthogonal protein surfaces for dimerization compared to cellular Erv sulfhydryl oxidases. In fact, the pB119L and Ac92 dimerization interfaces are orthogonal to one another as well [7], [10]. Here we present the structure of the intact mimivirus sulfhydryl oxidase R596, including both its sulfhydryl oxidase domain and its ORFan domain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Viruses with a deletion in ac92 or a mutation in the sequence CXXC (Wu and Passarelli, 2010), a sulfhydryl oxidase motif important for oxidation in cellular enzymes (Fass, 2008), exhibited similar phenotypes, suggesting a requirement for disulfide bond formation in the proper assembly and propagation of AcMNPV virions. The structure of Ac92 revealed that the arrangement of active-site cysteine residues and bound flavin adenine dinucleotide cofactor is similar to that observed in other Erv family sulfhydryl oxidases (Hakim et al, 2011). Although Ac92 is a functional sulfhydryl oxidase and its enzymatic activity is essential for proper ODV formation and BV production, the target substrate(s) of Ac92 during baculovirus infection is unknown.…”
Section: Introductionsupporting
confidence: 60%
“…In addition, the structure of a sulfhydryl oxidase from the NCLDV mimivirus has been derived (Hakim et al, 2012). The sulfhydryl oxidases of the baculoviruses Autographa californica M nucleopolyhedrovirus (AcMNPV), Ac92 (P33), and Bombyx mori NPV, Bm75, have also been characterized structurally (Hakim et al, 2011; Hou et al, 2012) and functionally (Hou et al, 2012; Nie et al, 2011; Wu and Passarelli, 2010). …”
Section: Introductionmentioning
confidence: 99%